2015
DOI: 10.1167/tvst.4.5.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transient Local Anti-inflammatory Treatment on the Survival of Pig Retinal Progenitor Cell Allotransplants

Abstract: Purpose: The development of photoreceptor replacement therapy for retinal degenerative disorders requires the identification of the optimal cell source and immunosuppressive regimen in a large animal model. Allotransplants are not acutely rejected in swine subretinal space, although it is not known if survival can be improved with immunosuppression. Here we investigated the survival and integration of expanded pig retinal progenitor cells (pRPCs) in normal recipients with and without transient anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…ReNeuron have developed an interesting technology, whereby foetal RPC can be expanded at least 40-fold in hypoxic conditions akin to that experienced in vivo, overcoming many of the supply problems in obtaining these cells from week 16 to week 18 human foetuses. Publications have suggested that in vitro expanded RPC have some ability to differentiate and express photoreceptor markers [ 97 99 ], but this is limited and differentiation after transplantation appears to be dependent on host conditions particularly maturity, with transplant into immature retinas being more successful than mature ones [ 100 102 ]. Furthermore, cell migration into the outer retina is variable and the predominant markers expressed by transplanted cells are glial [ 103 ].…”
Section: Sources Of Cells For Transplantationmentioning
confidence: 99%
“…ReNeuron have developed an interesting technology, whereby foetal RPC can be expanded at least 40-fold in hypoxic conditions akin to that experienced in vivo, overcoming many of the supply problems in obtaining these cells from week 16 to week 18 human foetuses. Publications have suggested that in vitro expanded RPC have some ability to differentiate and express photoreceptor markers [ 97 99 ], but this is limited and differentiation after transplantation appears to be dependent on host conditions particularly maturity, with transplant into immature retinas being more successful than mature ones [ 100 102 ]. Furthermore, cell migration into the outer retina is variable and the predominant markers expressed by transplanted cells are glial [ 103 ].…”
Section: Sources Of Cells For Transplantationmentioning
confidence: 99%
“…For xenograft studies, green fluorescent protein-positive (GFPþ) pig RPCs (pRPCs) from fetal pigs, transfected with a retroviral vector containing the gfp gene following a bactin promoter, were thawed from cryovials and cultured as described previously 22 . GFPþ pRPCs were chosen for easier detection of transplanted cells via immunostaining for GFP.…”
Section: Cell Culture Of Human Rpcs and Gfpþ Pig Rpcsmentioning
confidence: 99%
“…Culture protocol was identical to hRPCs, with the same media on a fibrinogen-coated flask. Prior to transplantation, pRPCs were suspended in Hank's balanced salt solution (HBSS) with N-acetylcysteine (NAC) at previously published concentrations, which was shown to enhance transplant survival due to antioxidant effects 22 .…”
Section: Cell Culture Of Human Rpcs and Gfpþ Pig Rpcsmentioning
confidence: 99%
“…Especially, relocation of an Intermediary 4-week phase of RPE separation maximum reliably conserved vision matched to mature or newer RPE cells [88]. Afterward, relocation seems to be reliant on host situations mainly in adulthood, with relocating to young retinas existing more fruitful than matured ones [89]. It is likely, nevertheless, that distinction, immigration, and existence might be better by modifications in transfer and host atmosphere [90].…”
Section: Photoreceptor Transplantationmentioning
confidence: 99%